Popular culture and the state in East and Southeast Asia - Otmazgin, Nissim; Ben-Ari, Eyal 1953- (Asia's transformations, 2012)
"This volume examines the relations between popular culture production and export and the state in East and Southeast Asia including the urban centres and middle-classes of Taiwan, South Korea, Japan, Singapore, Indonesia, Malaysia, China, Thailand, and the Philippines. It addresses the shift in official thinking toward the role of popular culture in the political life of states brought about by the massive circulation of cultural commodities and the possibilities for attaining soft power."--Publisher's description.